De tiende-eeuwse Heilig-Kruiskapel in Utrecht en haar relatie met Willibrord (Bulletin KNOB, 2008)
For centuries the Holy-Cross chapel (Heilig-Kruiskapel) stood between St Martin's cathedral church (domkerk or Sint-Maartenskerk) and St Saviour or Oldminster church (Sint-Salvatorkerk or Oudmunsterkerk) in Utrecht. In medieval historiography this cruciform little building was regarded as a church founded by the Anglo-Saxon missionary Willibrord at the end of the eighth century and devoted to the Holy Cross. According to the oldest historiography this church was situated next to St Martin's church that Willibrord had built on the foundations of an older church.After excavations since 1929 archaeologist A.E. Giffen concluded that the Holy-Cross chapel did not date from Willibrord's time but from the tenth or eleventh century. However, in 1992 te Utrecht archaeologist H.L. de Groot put forward the remarkable idea that the chapel did date from Willibrord's time after all and that it had to be a St Martin's church built by this missionary.In 1993 a renewed excavation of the chapel took place. Charcoal samples found in the masonry were dated by the 14C-dating method. The results pointed at a dating in the tenth or eleventh century, as suggested by Van Giffen. In 2000 this was further worked out in this periodical on archaeological grounds by archaeologist C.A.M. van Rooijen.However, the question remained why in the Middle Ages - already from the early twelfth century onward at least - the chapel was regarded as having been founded by Willibrord in the eighth century. This problem can be solved by assuming that the first St Saviour's church of Willibrord - to be equated with the Holy Cross and not with St Martin - consisted of (a part of) the former Roman main building, the principia. The clergy living in monastic community was also housed in this building.Indications for this are two nearly contemporary biographies of saints from the eighth century. One vita describes how the dying abbot Gregorius had himself taken in front of the church door, where he died shortly afterwards, and the other mentions that when he stayed in Utrecht the missionary Liudger often slept 'on the attic of the church of St Saviour that Willibrord had built'. These statements are more comprehensible when we assume that the church and monastery were in one and the same building, probably the principia dating back to Roman times.After this main building had been demolished in the tenth century, the Holy-Cross chapel was built from the reclaimed materials, half on top of the former main building. In later centuries people came to regard this chapel as a church built by Willibrord. initially as the first St Saviour's church, and since the seventeenth century, completely erroneously, as the first St Martin's church.